Project-Based Learning in Fostering Narrative Writing Skills in English Language Acquisition - Ismail, Ismail (Universitas Muhammadiyah Enrekang, 2023)
The study aims to evaluate the impact of Project-Based Learning (PBL) on the English narrative writing skills of second-semester students in the English Language Education program at Muhammadiyah University Enrekang, Indonesia. The research employs an experimental design, utilizing pretest and post-test scores as quantitative measures. The PBL intervention, focused on narrative writing, spans seven weeks, incorporating various aspects of writing skills. The study's location is Muhammadiyah University Enrekang, with a sample of 22 students from the English Education study program. Ethical considerations are addressed through informed consent from participants and relevant approvals. Data collection involves pre and post-tests, as well as writing portfolios assessed using rubrics. The intervention instrument includes a structured learning plan and activities, emphasizing collaboration, grammar, vocabulary, and narrative development. Analysis of the paired sample t-test reveals a statistically significant improvement in students' narrative writing skills after PBL implementation, with a p-value of 0.0005. The mean scores show a notable increase from 12.68 to 19.68. Detailed analysis indicates improvements in content construction and language use, with significant enhancements in grammar and word choice. The findings suggest that PBL positively impacts students' narrative writing skills, aligning with previous research. The study contributes insights for educators, curriculum developers, and policymakers seeking evidence-based practices to enhance English language education. The research emphasizes the relevance of innovative approaches, such as PBL, in shaping proficient and globally competent language learners.